Tópicos de automação industrial aplicados nas unidades geradoras hidráulicas da Usina Hidrelétrica de Curuá-Úna - CUNHA, Elton Figueredo (2018)
This work is divided into two parts, the first deals with the theoretical framework, expounding on programmable logic controllers, instrumentation and industrial networks. The second part of this knowledge is applied in an industrial plant, the hydroelectric plant Curuá-Una in Santarém in Pará State The reference chapters present the fundamentals of the topics covered, as well as the technologies currently used. The chapter dealing with the automation of hydraulic generating units exposes how and where technological devices which are based on the mentioned knowledge are used.